Modele intermediare în dialogul știință-religie - Gheorghe Răzmeriță (TheoRhēma, 2016)
The development of the theory of naturalistic evolution by modern science generated concern among the scientists, philosophers and theologians for whom this theory appeared too convincing, but for whom the existence of God and His intervention in the universe was too obvious to be rejected. This situation forced these scientists and theologians to propose various models of integration of science and religion or of creation and evolution. This article describes and evaluates these intermediary models.